A Gender Comparison of Motivations for Physical Dating Violence Among College Students. (January 2016) - Elmquist, JoAnna; Wolford-Clevenger, Caitlin; Zapor, Heather; Febres, Jeniimarie; Shorey, Ryan C.; Hamel, John; Stuart, Gregory L.
There are limited empirical investigations that directly compare men and women's motivations, or reasons, for perpetrating physical dating violence (DV). In an attempt to further understand whether men and women have similar or different motives for physical DV, the purpose of the current study was to conduct a gender comparison of motives in a sample of male ( n = 163) and female ( n = 319) college students. Motivations for physical DV were classified according to seven broad categories proposed by Langhinrichsen-Rohling and colleagues: (a) power/control, (b) self-defense, (c) expression of negative emotion (e.g., anger), (d) communication difficulties, (e) retaliation, (f) jealousy, and (g) other (e.g., because it was sexually arousing, the influence of alcohol, the influence of drugs). The prevalence of physical violence perpetration in the overall sample was 29.4%. Results indicated that communication difficulties and self-defense were among the most frequently endorsed motive categories for both male and female perpetrated DV. In addition, results demonstrated gender similarity in all of the examined motive categories. Research and clinical implications are discussed.